Ginsenoside Rg1 alleviates chronic testicular damage caused by cranial irradiation through the SCF/PI3K/Akt/mTOR pathway in mice - Qiuhua Zhou; Yiquan Ou; Xiangsheng Tian; Yujun Ning; Yuwei Mao; Weichao Zhao; Dingxin Long (Radiation Medicine and Protection, 2025)
Objective: To investigate whether Ginsenoside Rg1 can mitigate the adverse effects of cranial irradiation on distal reproductive function in mice and to explore the underlying mechanisms. Methods: Forty male C57BL/6J mice were randomly divided to four groups [Control, irradiation (IR), IR ​+ ​Rg1, Rg1), IR ​+ ​Rg1 and Rg1 group treated with intraperitoneal injections of Ginsenoside Rg1 for 30 ​d, followed by single-dose irradiation of 5 ​Gy X-ray irradiation (2 ​Gy/min) for the IR and IR ​+ ​Rg1 group. After three months, testicles, whole brain, and serum samples were collected for analysis. Results: Histological staining, transmission electron microscopy, sperm analysis, and immunofluorescence demonstrated that Ginsenoside Rg1 ameliorated structural and functional damage to the testicles, enhanced sperm count (IR: 20.70 ​± ​1.62 vs. IR ​+ ​Rg1: 33.93 ​± ​2.20, t ​= ​−13.23, P ​< ​0.05), and reduced sperm malformation rates (IR: 46.33 ​± ​2.18 vs. IR ​+ ​Rg1: 39.00 ​± ​1.67, t ​= ​7.33, P ​< ​0.05). Further Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) and Enzyme linked immunosorbent assay (ELISA) assays demonstrated that Rg1 inhibited testicular apoptosis (IR: 3.21 ​± ​0.28 vs. IR ​+ ​Rg1: 1.81 ​± ​0.18, t ​= ​1.40, P ​< ​0.05) and modulated serum testosterone (IR: 4.47 ​± ​0.23 vs. IR ​+ ​Rg1: 6.65 ​± ​0.09, t ​= ​−2.18, P ​< ​0.05), GnRH (IR: 24.37 ​± ​0.92 vs. IR ​+ ​Rg1: 32.98 ​± ​1.33, t ​= ​−8.61, P ​< ​0.05), and FSH levels (IR: 1.41 ​± ​0.11 vs. IR ​+ ​Rg1: 2.69 ​± ​0.21, t ​= ​−1.28, P ​< ​0.05). Additionally, quantitative PCR and Western blot showed that Rg1 downregulated SCF, p-PI3K, p-Akt, and mTOR protein expressions in irradiated mice. Conclusions: Ginsenoside Rg1 potentially alleviate chronic testicular structural and functional damage by inhibiting germ cell apoptosis through the modulation of the HPG axis and the PI3K/Akt/mTOR pathway, suggesting that it is a potential therapeutic agent for reproductive disorders induced by cranial irradiation.